2017
DOI: 10.4081/cp.2017.932
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Thyroid Hemorrhage on Chronic Anticoagulation Therapy

Abstract: Even though highly vascularized, the thyroid gland rarely has spontaneous bleeding. Bleeding into the thyroid gland can result in potentially lethal acute airway compromise. This case report describes an elderly patient on warfarin for atrial fibrillation, who presented with swelling on the right side of her neck causing acute airway obstruction. An urgent computed tomography of the neck showed an enlarging hemorrhage into the right lobe of the thyroid gland. She was initially intubated for airway protection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The risk of bleeding is increased due to immature angiogenesis, arteriovenous shunt, increased vascular flow, and thyroid gland fragility. Anticoagulants can also increase the severity of spontaneous bleeding ( 54 ). Elbers et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of bleeding is increased due to immature angiogenesis, arteriovenous shunt, increased vascular flow, and thyroid gland fragility. Anticoagulants can also increase the severity of spontaneous bleeding ( 54 ). Elbers et al.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of bleeding is increased due to immature angiogenesis, arteriovenous shunt, increased vascular flow, and thyroid gland fragility. Anticoagulants can also increase the severity of spontaneous bleeding (54). Elbers et al (55) indicated that low thyroid hormone concentrations could shift the hemostatic system towards hypocoagulability and a hyperfibrinolytic state, which may increase the bleeding risk.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for intraparenchymal bleeding include the use of anticoagulants [5,6], fibrinolytic therapy [7,8], trauma [9][10][11], and invasive diagnostic procedures such as thyroid needle biopsy [12][13][14], although rare cases of spontaneous bleeding have been described [15].…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid gland hemorrhage is a life-threatening situation if not managed promptly and correctly. Spontaneous intrathyroidal hemorrhage (ITH) causing airway obstruction is relatively rare and different causes are reported in the literature ( 1 , 2 , 3 , 4 ). Spontaneous hemorrhage of the thyroid gland usually occurs in cases with thyroid nodules and cysts; however, the reason for rupture is still not clear ( 2 , 4 , 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%